Cupuassu plant management and the market situation of Itacoatiara, Manacapuru and Presidente Figueiredo counties, Amazonas State, Brazil (Research, Society and Development, 2021)
Theobroma grandiflorum (Willd. ex Spreng. Schum.) is one of the most cultivated fruit species in the Amazon. This work analyzed three aspects of cultivation and fruit processing in the Amazonas State counties of Itacoatiara, Manacapuru and Presidente Figueiredo: the farms producing cupuassu, the utilization, and marketing forms of its byproducts. In these counties there is no uniformity in cupuassu plantations for plants density, fruit and seed yields. They were formed without proper guidance from State agencies agricultural assistance, resulting in very poor cultivation system, with high plants densities found in almost all rural properties. These high densities increase plants competition for nutrients and light, favor the pests and diseases proliferation and hinder harvesting. If farmers use technologies and proper techniques of cultivation and maintenance, cupuassu pulp productivities could increase from 442-649 (counties averages) to 2,000-3,000 kg.ha-1. Seed production jump from 0 (when not sold) or 178-261 (counties averages) to 1,000-1,257kg.ha-1.